2020
DOI: 10.3390/w12020313
|View full text |Cite
|
Sign up to set email alerts
|

Functional Groups of Phytoplankton and Their Relationship with Environmental Factors in the Restored Uzarzewskie Lake

Abstract: Uzarzewskie Lake is a small, postglacial lake, located in western Poland. The lake is under restoration treatment since 2006. At first, iron treatment was done for 2 years. In the second stage, spring water was directed into the hypolimnion in order to improve water oxygenation near the bottom sediments. The purpose of our research was to determine changes in the contribution of functional groups to the total number of taxa and total biomass of phytoplankton due to changes in the physical and chemical characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 52 publications
0
15
0
1
Order By: Relevance
“…Natural and anthropogenic flows are interconnected, which causes difficulties in distinguishing the actual "natural" and "anthropogenic" cycles (Odum, 1986). A number of authors have shown that the changes caused by the inflow of biogens into continental waters create conditions for the process of anthropogenic eutrophication, causing the restructuring of aquatic ecosystems (Kozak et al, 2020). There is also a great number of publications on the consequences of river-flow regulations, which caused changes in the hydrochemical and hydrophysical properties of waters (slowing of water exchange, decrease in the flow rate, changes in the N/P ratio, ionic composition) and analyses of factors determining phytoplankton succession.…”
Section: Discussionmentioning
confidence: 99%
“…Natural and anthropogenic flows are interconnected, which causes difficulties in distinguishing the actual "natural" and "anthropogenic" cycles (Odum, 1986). A number of authors have shown that the changes caused by the inflow of biogens into continental waters create conditions for the process of anthropogenic eutrophication, causing the restructuring of aquatic ecosystems (Kozak et al, 2020). There is also a great number of publications on the consequences of river-flow regulations, which caused changes in the hydrochemical and hydrophysical properties of waters (slowing of water exchange, decrease in the flow rate, changes in the N/P ratio, ionic composition) and analyses of factors determining phytoplankton succession.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that a high conductivity (1500 µS·cm −1 ) had a neutral or positive effect on growth for the R. raciborskii strain [ 43 ]. In other papers, it was shown that the water conductivity affected the abundance of selected microorganisms in both freshwater and seawater [ 44 , 45 ]. In our experiments, the initial conductivity of the medium was 760 µS·cm −1 , and without the addition of any living organism within 14 days it was stable ( Figure 3 A).…”
Section: Resultsmentioning
confidence: 99%
“…The advantage of moderate oxygenation over intensive oxygenation consists in limiting the mineralization of organic matter in bottom sediments, enabling nitrification and denitrification processes that result in the removal of nitrogen into the atmosphere, thus maintaining the positive redox potential at the sediment-water interface, which allows phosphorus retention. As a result, the nitrogen ammonium is oxidized to the form of N 2 , enabling the annamox process to occur [20,27,28,[31][32][33][34][35][36]. The pulverizing aerator uses only energy from a wind turbine (Savonius system) to drive the pulverizing unit.…”
Section: Pulverization Aeration Methodsmentioning
confidence: 99%